Binderless low silica X zeolite for methane separation from binary CO2/CH4 biogas stream: A comprehensive experimental and computational study - Yadav, Tushar R.; Shrotri, Aadesh R.; Kate, Pranjali N.; Devasia, George; Niphadkar, Prashant S.; Mali, Nilesh A.; Krishnamurty, Sailaja; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2025)
This study presents the synthesis of binderless Na-LSX (B-Na-LSX) and binderless NaK-LSX (B-NaK-LSX). XRD, SEM, EDS, and N-2 physisorption were used for characterization of samples. Computational modelling of prepared sorbent was performed for the fundamental understanding of zeolite topology and adsorption behaviour. The breakthrough experiments are used to evaluate the adsorption capacities on CO2/CH4 (40/60 vol%) binary biogas stream. The results were compared with commercial Na-LSX (C-Na-LSX). The breakthrough adsorption capacity of B-Na-LSX was 3.08 mmol g(-1) and 0.29 mmol g(-1) of CO2 and CH4, respectively, at 300 K and 1 bar. CO2 sorption capacity of B-Na-LSX was similar to 11 % and similar to 17 % higher than B-NaK-LSX (2.77 mmol g(-1)) and C-Na-LSX (2.56 mmol g(-1)), respectively. DFT study reveals that the higher adsorption of CO2 over CH4 was attributed to higher charge transfer from CO2 to zeolite framework. Dual-bed six-step Pressure Swing Adsorption (PSA) was performed on B-Na-LSX at 6 bar. similar to 232 cycles were run with above 98 % of CH4 purity and similar to 74 % of recovery. The life-cycle test of sorbent was studied. It was implied that the designed sorbent is effective to produce the high purity of CH4 and can be utilized for a longer period for CH4 production.
Keywords: Binderless; Biogas; LSX zeolite; methane; PSA; Separation

Cation-exchanged Al-substituted ETAS-10 for adsorption of CO2 and N2 - Birje, Amit R.; Yadav, Tushar R.; Nandanwar, Sachin U. (Industrial & Engineering Chemistry Research, 2026)
In this study, Al-substituted ETAS-10 was synthesized via a seed-assisted hydrothermal method by varying the Al:Ti molar ratio. The material was modified via ion exchange with Li+, Ca2+, K+, and Sr2+ cations to tailor its adsorption behavior. The structural, morphological, and textural properties of the synthesized adsorbents were characterized by using XRD, FE-SEM, HR-TEM, EDS, Raman spectroscopy, CO2-TPD, and N2 physisorption. Li+-ETAS-10 exhibited a higher surface area and stronger basic sites available for the CO2 adsorption compared to the studied samples. The equilibrium adsorption isotherms of CO2 and N2 were measured at 25 degrees C and pressures up to 20 bar. Among the studied samples, ETAS-10 with an Al/Ti ratio of 0.2 showed the highest CO2 uptake of 3.19 mmol/g at 20 bar. This performance was enhanced by Li+ cation exchange, which increased the CO2 capacity to 3.52 mmol/g due to improved microporosity and stronger electrostatic interactions between CO2 molecules and the small radii of the Li+ cation. The adsorption isotherms follow the Langmuir model, indicating that adsorption behavior aligns with Langmuir assumptions across the investigated pressure range. Overall, the results highlight the synergistic role of framework Al incorporation and targeted cation exchange in enhancing the CO2 adsorption performance of ETAS-10. These materials exhibit potential as adsorbents for capture/adsorption of CO2.